SOSIALISASI PENGGUNAAN LEMBAR KERJA SISWA UNTUK MENDUKUNG PROSES PEMBELAJARAN MATEMATIKA - Suci Dahlya Narpila; Rusi Ulfa Hasanah; Roslina Harahap; Lola Manda Sari; Della Amrina Yusra (PAKEM: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aimed to improve mathematics teachers’ competencies in utilizing Student Worksheets (Lembar Kerja Siswa/LKS) to support the learning process. The participants consisted of 10 mathematics teachers from Al Fattah Foundation Medan. The main problems identified included the conventional use of worksheets that had not yet encouraged active student participation. The program was implemented through three stages: preparation, implementation, and evaluation. The implementation stage involved socialization sessions, workshops, and mentoring on the development and application of activity-based worksheets. Evaluation was conducted using response questionnaires and classroom observations. The results indicated that 90% of the teachers reported that the program greatly helped them understand the use of worksheets in learning, 85% felt more confident in independently developing worksheets, and 88% stated that the use of worksheets increased students’ classroom engagement. These findings demonstrate that the community service program had a positive impact on enhancing teachers’ competencies and improving the quality of mathematics instruction at Al Fattah Foundation Medan